2014
DOI: 10.5935/1984-6835.20140082
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Metal Ions in Contraband Cigarettes in Brazil

Abstract: In Brazil, one out of each four cigarettes consumed by the smokers is smuggled. These cigarettes do not go through quality control and can present potential risk to their consumers. In this study, the flame atomic absorption spectrometry (FAAS) of metal ions Cu, Mn, Zn, Co, Cr, Cd, Pb, Fe, Ag and Ni was carried out in cigarettes of 18 different brands, which are the most smuggled into the country. The results obtained revealed that in all 18 brands of cigarettes analyzed, the values of metal ions under study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The lack of quality control of contraband cigarettes can be aggravating for public health. Cigarettes smuggled into Brazil have elevated concentration of heavy metals compared to legal cigarettes, with values up to eleven times higher for chromium (Cr), nickel (Ni), cadmium (Cd) and lead (Pb) [4]. Another study also showed the presence of fungi, insect parts, grass, and mites in smuggled cigarettes [5].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of quality control of contraband cigarettes can be aggravating for public health. Cigarettes smuggled into Brazil have elevated concentration of heavy metals compared to legal cigarettes, with values up to eleven times higher for chromium (Cr), nickel (Ni), cadmium (Cd) and lead (Pb) [4]. Another study also showed the presence of fungi, insect parts, grass, and mites in smuggled cigarettes [5].…”
Section: Introductionmentioning
confidence: 99%